Probabilistic Approach for Assessing Rock Mass Quality in the Tunnel - Panthi, Krishna Kanta (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Rock mass is a heterogeneous media and the quality of the rock mass may change within a very short distance. As a result, on many occasions considerable discrepancies (variations) have been found between the predicted and actual rock mass conditions along the tunnel alignment, resulting in signifi cant cost and time overruns. Finding innovative solutions for quantifying the quality of rock mass and assessing the risk of discrepancies are, therefore, key issues for cost effective and optimum tunneling solutions in the Himalayan region. In this paper, a probabilistic approach of uncertainty analysis has been proposed to evaluate the quality of rock mass based on the Q-system of rock mass classifi cation. Mapped rock mass quality data from the Modi headrace tunnel from Nepal have been used as a case study. The degree of correlation between the simulated results achieved by a probabilistic assessment using @Risk and values actually measured in the tunnel have been discussed. It is concluded that the probabilistic approach can be used as a tool in predicting rock mass quality and assessing risk in tunneling projects. DOI: http://dx.doi.org/10.3126/hn.v11i0.7154 Hydro Nepal Vol.11 2011 pp.6-11